2014
DOI: 10.1007/s11695-014-1275-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of PPI Use on Human Gut Microbiota and Weight Loss in Patients Undergoing Laparoscopic Roux-en-Y Gastric Bypass

Abstract: Laparoscopic Roux-en-Y gastric bypass (LRYGB) achieves sustainable weight loss possibly by altering the gut microbiota. The effect of a proton pump inhibitor (PPI) on weight loss and the gut microbiota has not been explored. PPI use and the gut microbiota were assessed before and 6 months after LRYGB in eight patients. Bacterial profiles were generated by 16S ribosomal RNA (rRNA) gene sequencing. Prior to LRYGB, PPI users had a higher percent relative abundance (PRA) of Firmicutes compared to nonusers. PPI use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 20 publications
2
31
1
1
Order By: Relevance
“…The role of PPIs in weight gain has been evaluated previously in the context of outcomes of postgastric bypass patients. A study of adult patients that underwent laparoscopic Roux-en-Y gastric bypass found that PPI users 6 months postgastric bypass trended towards less weight loss 44. This finding was postulated to be associated with PPI-induced changes in the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The role of PPIs in weight gain has been evaluated previously in the context of outcomes of postgastric bypass patients. A study of adult patients that underwent laparoscopic Roux-en-Y gastric bypass found that PPI users 6 months postgastric bypass trended towards less weight loss 44. This finding was postulated to be associated with PPI-induced changes in the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, weight loss is significantly associated with a decrease in the F/B ratio after Roux-en-Y gastric bypass surgery 25. Recently, one study have shown that perioperative PPI use was associated with an increase in Firmicutes and a decrease in Bacteroidetes in severely obese patients before and after laparoscopic Roux-en-Y gastric bypass surgery 26. The changes in bacterial composition in this study were similar to our results, with an increase of Firmicutes evident in the PPI-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…Its presence might be essential for a mucosal adherent network of beneficial microorganisms that together prompt these effects of the host. As a matter of fact, weight loss studies usually report increased abundance of Verrucomicrobia (mainly Akkermansia muciniphila) as well as several other microbial species (Liou et al 2013, Remely et al 2015, Ward et al 2014. Taken together, these results further indicate the possible importance of mucosa-associated microbial networks and their metabolic cross-feeding for regulation of host health-related parameters and prevention of disease.…”
Section: Chaptermentioning
confidence: 72%